A topology and sizing optimisation method for lightweight sandwich structures subject to dynamic and static constraints - Larsson, Johan; Göransson, Peter; Wennhage, Per (Composite structures, 2024)
A static-dynamic topology-sizing optimisation method is presented. The solution is based on a sequential Mixed-Integer Linear Programming solution and aims to minimise the mass of a structure subjected to concurrent constraints on static and dynamic response. It is shown that the classical problem of the dynamics of lightweight sandwich structures may be mitigated through core topology and face sheet thickness combinations, retaining the static load carrying capacity while presenting stringent dynamic properties at a low mass penalty. A numerical example, in the form of a load carrying sandwich beam which is excited at different frequencies, is used to demonstrate the method. •A topology-sizing optimisation method for lightweight sandwich materials is presented.•A constraint on the static compliance ensures the sandwich load carrying capacity.•The mass minimisation problem involves both core topology and face sheet thickness.•The optimisation is reformulated as a mixed integer linear programming problem.•Examples show that stringent dynamic constraints may be met at low mass penalty.